2021
DOI: 10.1371/journal.pgen.1009810
|View full text |Cite
|
Sign up to set email alerts
|

Selective sorting of ancestral introgression in maize and teosinte along an elevational cline

Abstract: While often deleterious, hybridization can also be a key source of genetic variation and pre-adapted haplotypes, enabling rapid evolution and niche expansion. Here we evaluate these opposing selection forces on introgressed ancestry between maize (Zea mays ssp. mays) and its wild teosinte relative, mexicana (Zea mays ssp. mexicana). Introgression from ecologically diverse teosinte may have facilitated maize’s global range expansion, in particular to challenging high elevation regions (> 1500 m). We generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 109 publications
(175 reference statements)
6
66
0
Order By: Relevance
“…We next evaluated correlations between minor parent ancestry and genomic features known to interact with selection in other hybrid systems. Studies in a number of systems have found that selection on hybrids can drive a positive correlation between recombination rate and minor parent ancestry [8,35,36,40]. Using averages of minor parent ancestry and recombination rate summarized in non-overlapping windows we found strong evidence that recombination rate is positively correlated with minor parent ancestry at both a local (Fig.…”
Section: Predictable Genomic Features Correlate With Minor Parent Ancestry In X Birchmanni ´ X Cortezi Hybrid Populationsmentioning
confidence: 70%
See 4 more Smart Citations
“…We next evaluated correlations between minor parent ancestry and genomic features known to interact with selection in other hybrid systems. Studies in a number of systems have found that selection on hybrids can drive a positive correlation between recombination rate and minor parent ancestry [8,35,36,40]. Using averages of minor parent ancestry and recombination rate summarized in non-overlapping windows we found strong evidence that recombination rate is positively correlated with minor parent ancestry at both a local (Fig.…”
Section: Predictable Genomic Features Correlate With Minor Parent Ancestry In X Birchmanni ´ X Cortezi Hybrid Populationsmentioning
confidence: 70%
“…Notably, three shared minor parent islands occur in inversions that differentiate species, conflicting with the prevailing wisdom that inversions should resist introgression (Fig. S18; see [40,56,57] for similar findings).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations